Composition and fate of triclosan in the sludge from wastewater treatment in Grahamstown, South Africa and Tiaret, Algeria - Ncube, Mbonisi (Rhodes University, Faculty of Pharmacy, Pharmacy, 2017)
Physicochemical properties such as pH, specific surface area (SSA), cationic exchange capacity (CEC), loss on ignition (LOI), pathogens, plant nutrients (nitrates, ammonium and phosphates), and heavy metals (manganese, copper, lead and cadmium) were determined for sewage sludge from Grahamstown and Tiaret. The values obtained were log transformed thereafter a t-test at 5 % level of significance was used to test for the difference in each parameter for both sludges. The pH of sludge was determined in 1:3 water, 16 water, 1:3 0.01 M calcium chloride and 1:3 1 M potassium chloride. The pH for Grahamstown and Tiaret sludge were in the ranges of 6.66-7.11 and 7.88-8.18 respectively. The SSA values for Grahamstown and Tiaret were 218 ± 108 and 261 ± 99.9 m2/g, and the CEC values were 119 ± 2.09 and 136 ± 6.03 mEq/100, respectively. The LOI values obtained were 1.33 ± 0.03 and 1.48 ± 0.11 % for Grahamstown and Tiaret, respectively. E. coll and heterotrophic bacteria were the pathogens determined, and were extracted from sludge using sterile saline and nutrient broth. The concentration of E. coll in Grahamstown and Tiaret sludge were 468 ± 7.63 and 7769 ± 1268 CFU/g d.w and for heterotrophic bacteria were 1.17x109 ± 7.42x108 and 1.43x109 ± 9.11 x108 CFU/g d.w. For Grahamstown sludge, the concentration of nitrates, ammonium and phosphates were 55.61 ± 55.20 mg/g d.w, 6.60 ± 2.36 mg/g d.w and 1.40 ± 0.30 mg/g d.w, respectively. For Tiaret sludge, the concentration of nitrates, ammonium and phosphates were 2.56 ± 2.90 mg/g d.w, 0.64 ± 0.45 mg/g d.w and 0.24 ± 0.19 mg/g d.w, respectively. The concentration of Mn, Cu, Pb and Cd in Grahamstown sludge were 423 ± 101, 353 ± 92, 40.2 ± 20 and 0.0 mg/kg d.w respectively, and for Tiaret sludge, the corresponding concentrations were 358± 295, 549±50, 1427± 1352 and 1.54 ± 0.61 mg/kg d.w. Sewage sludge was found to contain Triclosan, and solubility studies of the compound were conducted using sodium deoxycholate and sodium lithocholate. The apparent solubilities and rate constants indicated in brackets of TCS at 37 °C were 35.4 ± 1.21 mg/L (1.28 ± 0.36 Hr-) and 14.4 ± 0.34 mg/L (0.99 ± 0.17 Hr-) in sodium lithocholate and sodium deoxycholate, respectively. The apparent solubilities and rate constants indicated in brackets of TCS at 15 °C were 32.3 ± 0.88 mg/L (2.16 ± 0.80 Hr-) and 14.2 ± 0.39 mg/L (1.02 ± 0.17 Hr-) in sodium lithocholate and sodium deoxycholate, respectively. Triclosan was extracted from sludge using 1 g/L sodium deoxycholate and the determined concentration were 142 ± 33.5 gg/g d.w for Grahamstown sludge and 0-12 gg/g d.w for Tiaret sludge. Finally plant growth studies were conducted on radish and garden cress plants using Grahamstown sludge at 0, 20, 40, 80 and 100 % treatments. Statistical analysis (t-test and Kruskal-Wallis) at 5 % level of significance was done to compare growth parameters between control and different sludge treatments. For radish plants, the values for plant height, root length, number of leaves, leaf length and dry mass were 28.4-80-7 mm, 4.3-44.7 mm, 3.3-17.0 mm, 2.3-4.0 leaves and 6.3-15.3 %, respectively. For garden cress, the values for plant height, root length, number of leaves, leaf length and dry mass were 13.7-25.0 mm, 7.7-20.3 mm, 5.7-8.3 leaves, 3.0-8.3 mm and 8.8-15.0 %, respectively. Twenty percent (20 %) sludge treatment gave the best results in radish and garden cress plants with respect to plant height, root length, number of leaves and dry mass. Triclosan concentration in radish and garden cress plants was below the detection limit of 32.4 gg/g d.w.
Keywords: Sewage sludge; Sewage Purification -- South Africa Grahamstown; Sewage Purification Algeria Tiaret; Sewage sludge as fertilizer; Anti-infective agents